The Diagnostic Value of Radius Bone in Forensic Identification Using Radiographic Images in Iranian Population - Karimi Jeshni, Somayeh; Akhlaghi, Mitra; Varzandeh, Masoomeh (International Journal of Medical Toxicology and Forensic Medicine, 2018)
Background: Identification is an important and difficult part of forensic medicine. This study investigated the accuracy of using Maximum Length of Radius (MLR) and Maximum distal Width of Radius (MWR) measurements in radiographic images to determine sex in Iranian population. Moreover, the correlation between these parameters was evaluated. Methods: This study was carried out on radiographic images of 90 adults (45 men and 45 women) over 20 years old. The sample population was divided into three age groups of 20-34, 35-49, and ≥50 years old. Maximum length and width of radius were measured digitally and then analyzed. Results: The mean values of both measurements in men were more than those in women and radius length decreased with increasing age. The accuracy of these two measured parameters in determining sex was similar (83.3%). Moreover, the correlation values (r) between MLR and MWR were 0.49 (P<0.0001) in total studied population. Conclusion: Sex can be determined using MLR or MWR with relatively high accuracy. However, regarding the intermediate correlation between these values, it is not enough to estimate the corresponding MLR from MWR.